Satire in the Novel "Al-Fatḥal" by Zuhair Yassin Shlaibah (Journal of the College of Basic Education, 2025)
This research explores the theme of satire in narratives, specifically in the novel Al-Fatḥal by Zuhair Yassin Shleibah. The author employs satire to address political and social issues using various techniques, such as "parody," which features implicit sarcasm and humor to make sensitive and complex topics more accessible and easier for readers to comprehend. The author did not label his work as a "novel" on the cover, as is customary. In our view, this was not because he doubted its classification as a novel, but rather because he wanted to emphasize the satirical nature of the work, which is characteristic of parody. This designation is not a replacement or substitute for the novel itself! As we see, the late writer Adnan Al-Mubarak, who wrote the preface to this work, insisted on calling it a novel. The author portrays Iraqi society, its social phenomena, and the reality of Iraqis in exile through the character of Al-Fatḥal and those who mock him—individuals who fled the country for political or other reasons. For this reason, I chose to write about Al-Fatḥal, given the novelty, originality, seriousness, and significance of its theme. I am proud to say that I am the first to academically explore and analyze it. This study examines the concept of satire, its importance, motivations, and the cultural references employed by the novelist. It highlights different aspects of satire, including caricatured characters, sharp satire, comedic events, satirical language, witty remarks, and social and political critique through satire. I adopted a descriptive-analytical approach, which played a crucial role in explaining and accurately depicting the phenomenon of Al-Fatḥal, connecting real events with fictional elements.In conclusion, the study confirms that Al-Fatḥal represents a universal phenomenon present in both Western and Eastern societies